(untitled) (Journal of the College of Education for Women, 2019)
Includes search unemployment concept ... types, graduate unemployment a model introduction to the researcher tackled the problem of unemployment being dangerous to the community, it’s also growing in size year after year is a waste of a clear human capabilities, also addressed the importance of the research being a touch on the problem of unemployment and its concept and try to find solutions to them , and then came the goals set by the search researcher identifies unemployment and their causes and consequences and to provide a true picture of the situation of unemployed graduates and disclosure about how they treat their graduates for jobs provide him with a decent life problem. And adopted a researcher on the use of a questionnaire addressed a number of questions on the subject as well as conduct some interviews with this group and get to know their point of view on the subject of unemployment and the resulting, as has been relying on the descriptive approach the goal of the state registration description of the realities faced by this category.The first chapter discusses the concept of unemployment as a socio-economic phenomenon found with a human, especially in modern societies, also dealt with the historical roots of unemployment in Iraq and the current reality of unemployment and kinds.The second chapter practical side where he identified the researcher, questionnaire included ten questions were distributed to the research sample consisting of 200 unemployed graduates, were put answers in the table, then the questionnaire analysis and through, many of the recommendations that limit the practice of placing unemployment, including the provision of the state capital for the unemployed graduates to establish small-scale projects to meet theexpenses and the expenses of their families, bringing them the salaries of social care, and educating young people not to emigrate.